Supraorbital morphology and social dynamics in human evolution - Godinho, Ricardo Miguel (2018)
Uniquely, with respect to Middle Pleistocene hominins, anatomically modern humans do not possess marked browridges, and have a more vertical forehead with mobile eyebrows that play a key role in social signalling and communication. The presence and variability of browridges in archaic Homo species and their absence in ourselves have led to debate concerning their morphogenesis and function, with two main hypotheses being put forward: that browridge morphology is the result of the spatial relationship between the orbits and the brain case; and that browridge morphology is significantly impacted by biting mechanics. Here, we virtually manipulate the browridge morphology of an archaic hominin (Kabwe 1), showing that it is much larger than the minimum required to fulfil spatial demands and that browridge size has little impact on mechanical performance during biting. As browridge morphology in this fossil is not driven by spatial and mechanical requirements alone, the role of the supraorbital region in social communication is a potentially significant factor. We propose that conversion of the large browridges of our immediate ancestors to a more vertical frontal bone in modern humans allowed highly mobile eyebrows to display subtle affiliative emotions.